Teacher Quality and Learning Inequality - Kutscher, Macarena; Morales, Catalina; Riquelme, Cristina; Urzúa, Sergio (Estudios de Economía, 2025)
This paper explores the contribution of teachers to student performance in Chile’s college admission test (PSU). Our analysis is based on a unique teacher-student matched dataset and decomposition methods. The findings suggest that teachers’ performance on the PSU and the characteristics of their educational degrees are significant predictors of students’ success. When controlling for students’ and predetermined school characteristics, the gap between voucher and public schools is reduced. Productivity differences emerge as key factors driving the disparities across school types. The analysis underscores the crucial role of teacher-student interactions in shaping student outcomes.